The impact of digital trade on inclusive green growth—evidence from China’s experience - Chu, Yunfan; Du, Yijing; Yang, Yuetao (Frontiers in Environmental Science, 2025)
Inclusive green growth, as a form of green and shared growth, is an important way to promote the realization of the common prosperity of all people. As an emerging trade model, digital trade has had a profound impact on sustainable development and has become an important driving force for promoting inclusive green growth. Based on the panel data of 31 provinces in China from 2014 to 2021, this study introduces two research methods, EWM- TOPSIS and panel regression model, and utilizes the analysis of transmission mechanism and heterogeneity to deeply explore the impact of digital trade on inclusive green growth and its intrinsic mechanism under the perspective of spatial correlation. The results show that: (1) Digital trade effectively promotes inclusive green growth, and this conclusion is verified to be robust by excluding extreme values, and adding control variables. (2) Mechanism testing shows that digital trade can promote green and inclusive growth by optimizing the industrial structure. (3) Heterogeneity tests show that the enabling effect of digital trade is more pronounced in the eastern, central and western regions of China and at the 25%, 50% and 75% quintiles of inclusive green growth. Therefore, it is of great significance to use digital trade in the future to coordinate the development of inclusive green growth in various provinces and regions by optimizing the industrial structure, and to enhance the overall level of inclusive green growth and sustainable economic development.